Duty ratio modulation method to minimise torque and flux linkage ripples for IPMSM DTC system. Issue 17 (1st August 2017) - Yuan, Tianqing; Wang, Dazhi; Li, Yunlu; Tan, Sen; Zhou, Shuai
Abstract : The active vector effects on torque and stator flux linkage are different in direct torque control (DTC) system. These differences may cause the over‐compensation or under‐compensation to torque and flux linkage leading to large ripples. Aimed at making sure the system can work in an optimum state, a novel duty ratio modulation strategy minimising the torque and flux linkage ripples is designed. Every sector is divided into five small sectors, and a new switching table is designed. The impact factors and the active factors are first introduced into the DTC system. Subsequently, a novel duty ratio modulation method is derived. The superiority is verified through the simulation results.